Acute Response to Capsiate Supplementation at Rest and during Exercise on Energy Intake, Appetite, Metabolism, and Autonomic Function: A Randomized Trial - Rossi, Priscila A. Q. [UNESP]; Lira, Fabio S. [UNESP]; Bezerra, Vanessa R. [UNESP]; Clark, Nicolas W.; Fukuda, David H.; Panissa, Valéria L. G. (My University, 2021)
Objective: The purpose of the present study was to examine the effect of capsiate supplementation on energy intake, self-reported appetite-related sensations, energy expenditure, fat oxidation, and autonomic parameters with and without an exercise intervention. Methods: Thirteen healthy men completed four randomized trials: two trials for the control condition (without exercise), one with capsiate supplementation (CTRLcap) and one with a placebo (CTRLpla), and two trials for the exercise condition, one with capsiate supplementation (EXcap) and one with placebo (EXpla). Exercise sessions were performed 150 min after the consumption of a standardized breakfast, and supplementation 115 min after consumption of breakfast. An ad libitum buffet was offered 200 min following the completion of the standardized breakfast, and energy intake (EI) and relative energy intake (REI) (relative energy intake = energy intake - energy expenditure related to exercise) were evaluated. Results: There were no significant effects on EI, self-reported appetite sensations, fat oxidation, and energy expenditure. REI was reduced in conditions involving EX when compared to CTRL. A low-frequency to high-frequency ratio for heart rate variability was higher in CTRLcap (1.6 ± 1.1) vs. CTRLpla (1.2 ± 0.9) (p = 0.025; d = 0.39). Conclusion: Acute capsiate supplementation combined with aerobic exercise has limited effects on the examined variables (EI, REI, fat oxidation, energy expenditure, and autonomic parameters), while changes in the autonomic nervous system function in the absence of exercise may have occurred without influencing other variables. Clinical trial registration: ensaiosclinicos.gov.br number, RBR-5pckyr https://ensaiosclinicos.gov.br/rg/RBR-5pckyr.
Keywords: appetite; Heart rate variability; hunger; substrate oxidation; supplementation